Importance of Population Growth in Future Economic Development of Pakistan - Kumar, Mahendar (Advances in Social Sciences Research Journal, 2016)
Population growth is considered by most of the scholars an obstacle for economic development of any country as the resources are always limited. Therefore, this study is conducted to analyze the population growth in terms of old age security, cultural pressure and women empowerment in order to visualize its impact on future economic development of Pakistan. The study while quantitative in nature with complimentary qualitative features found at the end that there is a weak relationship between components of population growth and future economic development of Pakistan.